2018
DOI: 10.1016/j.jfoodeng.2017.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Moisture absorption kinetics of FruitPad for packaging of fresh strawberry

Abstract: This study analysed the moisture absorption kinetics of FruitPad embedded with different concentrations of fructose with further application of such pads in packaging of fresh strawberries. The FruitPad was exposed to different storage conditions (temperature and RH) and moisture absorption kinetics was gravimetrically determined over 5 days of storage. FruitPad with 30% fructose showed highest amount of moisture absorption (0.94 g of water/g of pad) at 20 °C and 100% RH. The Weibull model combined with the Fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…In addition, results showed that the fluctuating temperature led to a higher mass loss when compared with experiments carried out at 12°C for the same 5 days . Under constant temperature, with two microperforations of 0.7‐mm diameter, the percentage mass loss of strawberries was 0.92%, 0.62%, 0.26%, and 0.21%, which represents an increase of 1.4, 1.7, 2.7, and 2.9 times higher for FP‐30, FP‐20, FP‐00, and control, respectively.…”
Section: Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…In addition, results showed that the fluctuating temperature led to a higher mass loss when compared with experiments carried out at 12°C for the same 5 days . Under constant temperature, with two microperforations of 0.7‐mm diameter, the percentage mass loss of strawberries was 0.92%, 0.62%, 0.26%, and 0.21%, which represents an increase of 1.4, 1.7, 2.7, and 2.9 times higher for FP‐30, FP‐20, FP‐00, and control, respectively.…”
Section: Resultsmentioning
confidence: 79%
“…FruitPads incorporated with varying fructose content (as active absorbing component) were used to evaluate package performance under the fluctuating temperature. The structure of the Fruitpads (McAirLaid's Vliesstoffe GmbH, Steinfurt, Germany) is as described in Bovi et al Package types were named according to the percentage of fructose contained were FP‐00, FP‐20, FP‐30, FP‐35, and FP‐40 for FruitPad containing 0%, 20%, 30%, 35%, and 40% of fructose, respectively. For comparison purpose, other packaging materials with relatively high WVTR such as Xtend film (StePac, Tefen, Israel) and cellulose‐based biodegradable NatureFlex film (Innovia Films, Cumbria, UK) were used (Table ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations